Periodontal management of the elderly with medical compromise: a case report - Ira A. Sembiring; Andi M. Adam (Journal of Dentomaxillofacial Science, 2019)
Objective: The aim of the periodontal treatment is to provide healthy and functional dentition all through a lifetime. The primary objective of this case report is to describe that periodontal disease in the elderly complicated by medical compromise should be treated and the results will be very satisfactory.Methods: Female 68 year old with cardiovascular disease took Amlodipine and Aspirin medication since two months ago. Patients complained of enlarged gingiva, all of the teeth become mobility. Periodontal surgery is performed by previously referring back to the internist to prepare patient condition facing periodontal surgery.Results: After several fase periodontal treatment, the gingival inflamation demonstrated a good control and periodontal status become more stable.Conclusion: Although managing periodontal disease in elderly is complicated, the proper control of the periodontal infection and inclusion of other healthcare professionals will improve the prognosis and get a satisfactory result. In fact, studies demonstrate that elderly individuals whose comprehensive management includes dental care develop fewer co-morbid conditions and require less expenditure of healthcare rupiahs.